Tunable Self-Assembled Nanostructures of Electroactive PEGylated Tetra(Aniline) Based ABA Triblock Structures in Aqueous Medium - Mushtaq, Irrum; Akhter, Zareen; Shah, Faiz Ullah (Frontiers in Chemistry, 2019)
PEGylated tetra(aniline) ABA triblock structure PEG-TANI-PEG (2) consisting of tetra(aniline) (TANI) and polyethylene glycol (PEG) was synthesized by coupling the tosylated-PEG to boc-protected NH2/NH2 TANI (1) through a simple nucleophilic substitution reaction. Deprotection of 2 resulted in a leucoemeraldine base state of TANI (2-LEB), which was oxidized to stable emeraldine base (2-EB) state. 2-EB was doped with 1M HCl to emeraldine salt (2-ES) state. FTIR, 1H and 13C NMR and UV-Vis-NIR spectroscopy, MS (ESI) was used for structural characterization. Electroactivity of the polymeric materials was confirmed by CV. The triblock structures self-assembled in water were assessed by DLS, TEM, and SEM. Spherical aggregates were observed with variable sizes depicting the effect of concentration and oxidation of 2-LEB. Further, the aggregates showed acid/base sensitivity as evaluated by doping and dedoping of 2-EB with 1M HCl and 1M NH4OH, respectively. Future applications in drug delivery and sensors are envisaged for such polymeric materials tunable self-assembled nanostructures in aqueous media.